The versatility of Helicobacter pylori CagA effector protein functions: The master key hypothesis. - Backert, Steffen; Tegtmeyer, Nicole; Selbach, Matthias (Helicobacter, 2010)
Several bacterial pathogens inject virulence proteins into host target cells that are substrates of eukaryotic tyrosine kinases. One of the key examples is the Helicobacter pylori CagA effector protein which is translocated by a type-IV secretion system. Injected CagA becomes tyrosine-phosphorylated on EPIYA sequence motifs by Src and Abl family kinases. CagA then binds to and activates/inactivates multiple signaling proteins in a phosphorylation-dependent and phosphorylation-independent manner. A recent proteomic screen systematically identified eukaryotic binding partners of the EPIYA phosphorylation sites of CagA and similar sites in other bacterial effectors by high-resolution mass spectrometry. Individual phosphorylation sites recruited a surprisingly high number of interaction partners suggesting that each phosphorylation site can interfere with many downstream pathways. We now count 20 reported cellular binding partners of CagA, which represents the highest quantitiy among all yet known virulence-associated effector proteins in the microbial world. This complexity generates a highly remarkable and puzzling scenario. In addition, the first crystal structure of CagA provided us with new information on the function of this important virulence determinant. Here we review the recent advances in characterizing the multiple binding signaling activities of CagA. Injected CagA can act as a 'master key' that evolved the ability to highjack multiple host cell signalling cascades, which include the induction of membrane dynamics, actin-cytoskeletal rearrangements and the disruption of cell-to-cell junctions as well as proliferative, pro-inflammatory and anti-apoptotic nuclear responses. The discovery that different pathogens use this common strategy to subvert host cell functions suggests that more examples will emerge soon.